2008
DOI: 10.1038/clpt.2008.61
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants of the Organic Cation Transporter 2 Influence the Disposition of Metformin

Abstract: Genetic variants of the organic cation transporter 2 (protein, OCT2; gene, SLC22A2) were evaluated for their contribution to the variations in the pharmacokinetics of metformin, especially to its renal elimination. Genetic variants of SLC22A2 (c.596C>T, c.602C>T, and c.808G>T) showed significant differences in metformin pharmacokinetics when compared with the reference genotype, with higher peak plasma concentration (C(max)) and area under the curve (AUC) and lower renal clearance (Cl(renal)), thereby suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
173
7
5

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(192 citation statements)
references
References 19 publications
7
173
7
5
Order By: Relevance
“…14 Recent studies of OCT have demonstrated that polymorphisms of the OCT1 gene in Caucasians and the renal OCT2 gene in Koreans are responsible for the interindividual differences in the therapeutic efficacy and pharmacokinetics of metformin, an anti-diabetic agent. [15][16][17] Metformin showed large interindividual variation in renal clearance, and a potential genetic contribution by the renal transporter was speculated. 18 Because metformin is also a superior substrate for MATE1 and MATE2-K, 10,19 polymorphisms of MATE1 and MATE2-K genes may be involved in the interindividual difference in the renal clearance.…”
Section: Introductionmentioning
confidence: 99%
“…14 Recent studies of OCT have demonstrated that polymorphisms of the OCT1 gene in Caucasians and the renal OCT2 gene in Koreans are responsible for the interindividual differences in the therapeutic efficacy and pharmacokinetics of metformin, an anti-diabetic agent. [15][16][17] Metformin showed large interindividual variation in renal clearance, and a potential genetic contribution by the renal transporter was speculated. 18 Because metformin is also a superior substrate for MATE1 and MATE2-K, 10,19 polymorphisms of MATE1 and MATE2-K genes may be involved in the interindividual difference in the renal clearance.…”
Section: Introductionmentioning
confidence: 99%
“…Homozygous carriers of the low activity SLC22A2 variant, 270S, were reported to have significantly lower rates of renal clearance and higher plasma concentration of metformin than those homozygous for the active variant, 270A. 11,29 On the other hand, low-function SLC22A1 variants including R61C, G401S and G465R have been associated with significantly higher rates of renal clearance of metformin. 30 In addition to the effect on metformin pharmacokinetics, low-function SLC22A1 variants have been also associated with significantly decreased glucose-lowering response of metformin.…”
Section: Resultsmentioning
confidence: 99%
“…2,9,10 Among SLC22A2 variants, A270S is associated with differences in metformin blood levels and renal excretion, and R400C and K432Q have significant roles in altered activity of SLC22A2. 11,12 Located on 11q13.1-q13.2, organic anion transporter, SLC22A6, has been shown to transport methotrexate (cytotoxic antimetabolite used for rheumatoid arthritis, psoriasis and cancer of various types) and to be inhibited by non-steroidal anti-inflammatory drugs. 13,14 The R50H variant in SLC22A6 is associated with kinetic differences for the nucleoside phosphonate analogs adefovir, cidofovir and tenofovir.…”
Section: Introductionmentioning
confidence: 99%
“…2 OCT polymorphisms have been extensively studied in the context of metformin pharmacokinetics and response. 3,[5][6][7][8][9][10][11][12][13][14] Metformin is widely prescribed to treat diabetes mellitus type 2, with considerable variability in efficacy. Reduced-function OCT1 alleles-OCT1-Arg61Cys, OCT1-Gly401Ser, OCT1-420del, and OCT1-Gly465Arg-have been demonstrated by Shu and colleagues 8 to increase systemic exposure to metformin.…”
mentioning
confidence: 99%
“…The contribution of hepatic OCT3 expression versus enteric OCT3 expression to plasma metformin levels with respect to the hepatic concentration is not yet clear. Polymorphisms in renally expressed OCT2 have been associated with metformin pharmacokinetics, 13 and polymorphisms in the cation transporter MATE1 have also been associated with metformin efficacy in a diabetic population. 16 Most recently, Tzvetkov and colleagues 14 reported that polymorphisms of OCT1, but not OCT2 or OCT3, play a significant role in the renal clearance of metformin.…”
mentioning
confidence: 99%